# Find the x-intercepts. y=x^2-4x+4. Thanks for helping. All of this Algebra has lost me.

## To find the x-intercepts of a quadratic equation, we need to determine the values of x for which the equation equals zero. In your case, the equation is y = x^2 - 4x + 4.

To find the x-intercepts, we set y to zero and solve for x. So, we substitute y with zero in the equation:

0 = x^2 - 4x + 4

Now, we can solve this quadratic equation. There are several methods to do this, but one common method is factoring. However, in this case, the equation cannot be factored easily.

x = (-b ± √(b^2 - 4ac))/(2a)

Where a, b, and c are the coefficients of the quadratic equation in the form ax^2 + bx + c = 0.

In our equation, a = 1, b = -4, and c = 4. Plugging these values into the quadratic formula, we have:

x = (-(-4) ± √((-4)^2 - 4(1)(4))) / (2(1))

Simplifying further gives us:

x = (4 ± √(16 - 16)) / 2

x = (4 ± √0) / 2

x = (4 ± 0) / 2

x = 4 / 2

So, the x-intercept of the given quadratic equation is x = 2.

Therefore, the solution is that the graph of the equation y = x^2 - 4x + 4 has a single x-intercept at x = 2.